Association between smartphone usage and health outcomes of adolescents: A propensity analysis using the Korea youth risk behavior survey. - Jong Ho Cha; Young-Jin Choi; Soorack Ryu; Jin-Hwa Moon (PLoS ONE, 2023)
Objectives We aimed to investigate the association between smartphone use and adverse behavioral health outcomes using nationwide Korea Youth Risk Behavior Web-based Survey data for 2017 and 2020. Methods The 2020 data (N = 54,809) were used to analyze the relationships between daily smartphone usage time (non-user, 0-2 h [hour], 2-4 h, 4-6 h, 6-8 h, and > 8 h), and adverse health outcomes (stress, sleep, depression, suicide, substance use, and smartphone overdependence). A 1:1 propensity score matching (PSM) was used to control for confounding variables. Results A total of 40,998 adolescents with < 4 h/day and > 4 h/day of usage were included. Adolescents' mean smartphone usage time in 2020 increased compared to that in 2017 (weighted % of > 2 h/day; 64.3% vs. 85.7%). The curvilinear relationships between smartphone usage time and adverse health outcomes were prominent after > 4 h/day. Adolescents using smartphones 2-4 h/day showed no increased adverse health outcomes compared to non-users, except for smartphone overdependence. Using a smartphone > 4 h/day was significantly associated with stress perception (1.16; 1.11-1.22), suicidal ideation (1.22; 1.13-1.31), and substance use (alcohol, 1.66; 1.57-1.75) after PSM. Conclusions Our study demonstrated the curvilinear relationship between smartphone usage time and adverse health outcomes in adolescents. Our findings can help establish smartphone usage guidelines for adolescents.